2013
DOI: 10.2987/13-6331r.1
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Tests of the Residual Effect of Deltamethrin on Vegetation Against Aedes albopictus

Abstract: Aedes albopictus, the Asian tiger mosquito, was 1st detected in Spain in 2004 and since then has spread along the Mediterranean coast. New adulticiding strategies are being tested to enhance control of the species. The residual effect of applications of 2 formulations containing deltamethrin over vegetation was evaluated in bioassay tests for 34 days. Hedera helix plants were treated with K-othrine SC25 (deltamethrin 2.56% SC) and Aqua K-othrine (deltamethrin 2.03% EW). Bioassays consisted of exposing batches … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…The effect of insecticide-treated vegetation on Ae albopictus was reported 20 using K-othrine SC 25 (deltamethrin 2.56%) and Aqua K-othrine (deltamethrin 2.03%) in Spain. Applications to vegetation in plots were made using a hand compression Solo 423 backpack sprayer and mosquitoes were exposed to treated leaves in the laboratory.…”
Section: Bioassays and Semi-field Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of insecticide-treated vegetation on Ae albopictus was reported 20 using K-othrine SC 25 (deltamethrin 2.56%) and Aqua K-othrine (deltamethrin 2.03%) in Spain. Applications to vegetation in plots were made using a hand compression Solo 423 backpack sprayer and mosquitoes were exposed to treated leaves in the laboratory.…”
Section: Bioassays and Semi-field Studiesmentioning
confidence: 99%
“…Compared with studies in the United States with deltamethrin, the mortality period was shorter, with mortality for Aqua K-othrine-treated plants out to 12 days, and 5 days for K-othrine-treated plants. 20 In semi-field cages, 21 male and female Ae albopictus were exposed to wax myrtle plants treated with 1 of 6 products: Cy-kick CS (6% Cyfluthrin), Masterline (7.9% bifenthrin), Tempo SC Ultra (11.8% β-cyfluthrin), Demand CS (9.7% lambda-cyhalothrin), Suspend SC (4.75% deltamethrin), and Talstar P (7.9% bifenthrin). Leaves were treated to maximum label rates of each insecticide using a 700 mL spray bottle.…”
Section: Bioassays and Semi-field Studiesmentioning
confidence: 99%
“…The main mosquito control programs have been developed in Catalonia. For example, in the Baix Llobregat comarca (county), the integrated vector management includes community-based information plans and application of larvicides and adulticides [ 75 ]. In Sant Cugat del Vallés, Abramides et al [ 76 ] combined four control measures, including application of larvicides and adulticides, public cooperation for source removal and cleaning of landfills, finding a significant reduction of oviposition.…”
Section: Reviewmentioning
confidence: 99%
“…Also, some tests of biocides have been conducted in Spain. Bengoa et al tested residual pyrethroids on plants to act as chemical barrier against adults [ 75 ] and ultra-low volume (ULV) method with pyrethroids [ 78 ]. Both tests resulted in effective outcomes.…”
Section: Reviewmentioning
confidence: 99%
“…Due to its longer environmental persistence, it needs to be applied less often, but it is more likely to result in chronic exposure. When tested as a residual barrier applied on vegetation, laboratory results indicated that deltamethrin allowed reasonable control of 80% of the mosquitoes resting in vegetation for almost two weeks after initial application (Bengoa et al 2013). Deltamethrin has also been approved by the WHO as a safe residual treatment for bed nets (Ehiri et al 2004;Bengoa et al 2013).…”
Section: Exposurementioning
confidence: 99%